Export Procedure for Frozen Cooked Tuna (Thunnus sp.) Loin - Wartini, Sri; Widyastuti, Rida; Mahargyo, Dhady Pelita; Sasongko, Dimas Bayu; Nugraha, Jefri Putri; Laily, Nur (LPPM Universitas Ekasakti, 2024)
This study aims to analyze the export procedure of cooked frozen tuna loin (Thunnus sp.) at PT LSS Banyuwangi, a tuna product that is highly sought after in international markets. The research method used includes observation, interviews, and documentation to collect primary and secondary data. The results show that the export procedure of cooked frozen tuna loin involves several stages, from production preparation to shipment to international consumers. This process includes quality inspection, health and food safety certification, packaging, and transportation using a cold chain system to maintain product freshness. This study also discusses the required documents, such as export permits, health certificates, and regulatory documents from the destination country. Therefore, to improve export efficiency and success, companies need to ensure that each stage of the procedure is carried out correctly and in accordance with international standards to ensure that the product reaches consumers with the best quality.